ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2016) - Intan Dwi Safitri, 14.05.52.0216; Susilowati, Yeye (Students' Journal of Accounting and Banking, 2018)
The purpose of this study aims to examine and analyze the impact of Return on Investment, Debt to Equity Ratio, Earning Per Share, dan Current Ratio, toward stock return of manufacture companies that listed in Indonesia Stock Exchange for period 2014-2016. The sample of this study was obtained by purposive sampling method and consisted of 86 manufacturing companies listed in Indonesia Stock Exchange during the period from 2014-2016. The technique of data analysis is used multiple regression analysis with interation method. The results of this study shows that Return on Investment and Earning Per Share have a positive and don’t have a significance effect toward stock return. Debt to Equity Ratio and Current Ratio have a positive and has a significance effect toward stock return.Keywords : Return on Investment, Debt to Equity Ratio, Earning Per Share, Current Ratio and stock Return.